WEBVTT
00:00:00.870 --> 00:00:12.110
Find the missing term in the equation negative one-third multiplied by two-ninths is equal to something multiplied by negative one-third.
00:00:13.360 --> 00:00:19.640
In order to answer this question, we need to remember the commutative property of multiplication.
00:00:20.740 --> 00:00:26.840
This states that π multiplied by π is equal to π multiplied by π.
00:00:28.040 --> 00:00:33.280
For example, five multiplied by seven is equal to 35.
00:00:33.960 --> 00:00:38.490
And, seven multiplied by five is also equal to 35.
00:00:39.520 --> 00:00:43.400
It doesnβt matter which order we multiply two terms.
00:00:43.600 --> 00:00:45.820
The answer will still be the same.
00:00:46.860 --> 00:00:52.750
In this particular question, we have negative one-third on both sides of the equation.
00:00:53.670 --> 00:01:03.000
Multiplying negative one-third by two-ninths must give us the same answer as multiplying two-ninths by negative one-third.
00:01:04.190 --> 00:01:09.800
We can therefore conclude that the missing term in the equation is two-ninths.
00:01:11.070 --> 00:01:19.730
We could check this by firstly multiplying the two fractions on the left-hand side and then the two fractions on the right-hand side.
00:01:21.030 --> 00:01:28.550
In order to multiply two fractions, we multiply the two numerators, and then separately, the two denominators.
00:01:29.250 --> 00:01:33.400
Negative one multiplied by two is equal to negative two.
00:01:33.890 --> 00:01:37.800
And, three multiplied by nine is equal to 27.
00:01:39.010 --> 00:01:46.880
This means that negative one-third multiplied by two-ninths is equal to negative two over 27.
00:01:47.880 --> 00:01:58.430
Multiplying the two fractions, two-ninths and negative one-third, in the opposite order also gives us an answer of negative two over 27.
00:01:59.530 --> 00:02:04.060
This proves that we did have the correct missing term of two-ninths.